Nairobi Declaration: Commitments to enhance soil health - African Union Development Agency-NEPAD; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This poster introduces the Nairobi Declaration on the Africa Fertilizer and Soil Health (AFSH) Summit and gives the commitments on soil health made by the African Heads of State and Government with the aim to reverse land degradation and restore soil health on at least 30% of degraded soil by 2034. Commitments include deploying innovative incentive mechanisms, promoting integrated soil and water conservation, promoting investment in irrigation as part of integrated soil and water resource management, strengthening collaborative research and extension systems, and promoting organic agriculture practices.